Long‐lived high‐T, low‐P granulite facies metamorphism in the Arunta Region, central Australia. (31st October 2013) - Morrissey, L. J.; Hand, M.; Raimondo, T.; Kelsey, D. E.
Abstract In situ LA–ICP–MS U–Pb monazite geochronology from the Boothby Hills in the Aileron Province, central Australia, indicates that the region records more than 80 Ma of high‐T, low‐P (HTLP) anatectic conditions during the Early Mesoproterozoic. Monazite ages from granulite facies rocks and leucosomes span the interval 1576–1542 Ma. Pegmatites that overprint the regional gneissic fabric and are interpreted to record the last vestiges of melt crystallization give ages between 1523 and 1513 Ma. Calculated P–T pseudosections suggest peak metamorphic conditions in excess of 850 °C at 0.65–0.75 GPa. The retrograde evolution was characterized by a P–T path that involved minor decompression and then cooling, culminating with the development of andalusite. Integration of the geochronological data set with the inferred P–T path trajectory suggests that suprasolidus cooling must have been slow, in the order of 2.5–4 °C Ma−1. In addition, the retrograde P–T path trajectory suggests that HTLP conditions were generated within crust of relatively normal thickness. Despite the long duration over which anatectic conditions occurred, there is no evidence for external magmatic inputs or evidence that HTLP conditions were associated with long‐lived extension. Instead, it seems probable that the long‐lived HTLP metamorphism was driven to a significant extent by long‐lived conductive heating provided by high crustal heat production in voluminous pre‐metamorphic granitic rocks.